Optimizing DC Motor Control for Energy Efficiency in the Maritime Community with Linear Quadratic Regulator and Linear Quadratic Tracking Based on MATLAB Simulink - Imam Mursyid Muttaqin (Politeknik Perkapalan Negeri Surabaya, 2024)
This paper presents a comparative analysis between classical control techniques, such as Linear Quadratic Regulator (LQR), and modern control methods applied to motor control systems (Taini & Triwiyatno, 2019). Motor control systems are essential components in modern systems, requiring linear control strategies to optimize motor performance, particularly when faced with noise or operational disturbances. Traditionally, the Linear Quadratic Regulator (LQR) has been widely utilized. However, under certain conditions, its performance is deemed suboptimal (Riski Hanifa et al., 2018). As a result, there is a growing need for the development of more advanced and efficient control techniques, such as the feedback Linear Quadratic Tracking (LQT) method (Albar, 2018). A comparative analysis of performance response times under noisy conditions was simulated using MATLAB/Simulink. The simulation results show that the LQT control method outperforms LQR in terms of response time, exhibiting fewer overshoot and undershoot phenomena when noise is introduced before reaching the settling time (Andria et al., 2014). On the other hand, the LQR control method generates a transient response with a 0.7% overshoot before reaching the settling time. The Linear Quadratic Tracking (LQT) method, which is designed to track a predefined input path, successfully controls the system's output by adjusting the motor's speed and position. This method is especially useful for ensuring stability and minimizing disturbances during operation, even when faced with external noise. The results indicate that both LQR and LQT controllers were able to track the desired inputs effectively, maintaining stable performance despite their individual limitations. This study contributes to advancing the practical application of control systems in maritime communities, where motor efficiency and stability are crucial for supporting economic empowerment and sustainability in small-scale maritime operations.